2011
DOI: 10.5216/cab.v12i1.8986
|View full text |Cite
|
Sign up to set email alerts
|

AVALIAÇÃO ERITROCITÁRIA E BIOQUÍMICA DE JUNDIÁS (Rhamdia quelen) SUBMETIDOS À DIETA COM DIFERENTES NÍVEIS PROTÉICOS E ENERGÉTICOS

Abstract: linha seguidas de letras distintas diferem (P<0,05) pelo teste de Duncan. ** Proteína plasmática total.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
3
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 9 publications
2
5
3
6
Order By: Relevance
“…No significant difference was observed for triglycerides. Higuchi et al (2011) detected greater values than those observed in this study in which the total albumin and proteins levels in jundiá (R. quelen) fed with different protein levels ranged from 3.32 to 4.42, and from 6.92 to 5.78 g.dL -1 , respectively. Biochemical analyses in the blood aimed at evaluating its chemical components.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…No significant difference was observed for triglycerides. Higuchi et al (2011) detected greater values than those observed in this study in which the total albumin and proteins levels in jundiá (R. quelen) fed with different protein levels ranged from 3.32 to 4.42, and from 6.92 to 5.78 g.dL -1 , respectively. Biochemical analyses in the blood aimed at evaluating its chemical components.…”
Section: Discussioncontrasting
confidence: 83%
“…The erythrogram is a red series where the red blood cells present a pink tinge, are devoid of nucleus, and show dimensions similar to the ones in healthy fish. The erythrocyte related parameters were similar to those observed in jundiá (R. quelen) fed with different protein levels (from 1.98 to 2.21 x 10 6 ) (Higuchi et al, 2011). Chagas and Val (2003) observed that decreased hematocrit could characterize anemia in fish submitted to food deprivation when evaluating hematological parameters in tambaqui (Colossoma macropomum).…”
Section: Discussionsupporting
confidence: 74%
“…According to Higuchi et al (2011), the biochemical plasma parameters detected disorders in the functioning of organs and animal adaptations before stress conditions, where glucose is a indicative parameter of physiological changes, since it is the main source of energy used by fish to withstand adverse conditions (Morgan & Iwana, 1997;Urbinatti et al, 2004). Thus, the smallest amount of blood glucose of the tilapias subjected to 6 minutes of pre-slaughter hypoxia increased the use of this molecule in biochemical reactions in the body.…”
Section: Blood Biochemical Parametersmentioning
confidence: 99%
“…É possível avaliar o estado nutricional e de saúde dos peixes por meio de análise das características hematológicas, pois o sangue é um dos tecidos mais dinâmicos do organismo e reflete alterações da dieta (HIGUCHI et al, 2011). O conhecimento dos valores médios dos parâmetros hematológicos na natureza ou nos mais diversos sistemas de criação é importante para identificar as alterações fisiológicas derivadas da nutrição desses animais (ARAÚJO et al, 2011).…”
Section: The Objective Of This Study Was To Analyze the Influence Of unclassified
“…A composição bioquímica do plasma sanguíneo mostra a situação metabólica dos tecidos animais, sendo, por meio dela, possível detectar alterações no funcionamento dos órgãos e a adaptação do animal diante dos desafios nutricionais, fisiológicos e desequilíbrios metabólicos, específicos ou de origem nutricional (HIGUCHI et al, 2011). No EXP I, não foram obtidas diferenças significativas para os triglicerídeos, aminoácidos livres, albumina, colesterol total e proteínas totais, apenas foram observados menores níveis de glicose no plasma nos peixes alimentados com FCJSV, em relação aos com FCO (Tabela 2).…”
Section: Tabela 1 -Dietas Utilizadas Nos Experimentos I (Exp I) E Ii unclassified